Comparative Test of Pesticide Residues in Baby Oranges (Citrus sinensis) in Traditional and Modern Markets of Surabaya City: Uji Perbandingan Residu Pestisida pada Jeruk Baby (Citrus sinensis) di Pasar Tradisional dan Modern Kota Surabaya - Jihan Akhsania; Dwi Haryanta; Achmadi Susilo (Journal of Applied Plant Technology, 2026)
The use of pesticides in the cultivation of baby oranges (Citrus sinensis) is intended to control pests and diseases; however, it may leave residues on the fruit that can affect food safety. This study aimed to compare pesticide residue levels in baby oranges marketed in traditional and modern markets in Surabaya City and to assess their safety based on the applicable maximum residue limits (MRLs). The study was conducted in October 2025 using a survey approach and laborator analysis. Orange samples were collected from Keputran Market as a representative of traditional markets and Hokky Fruit Supermarket as a representative of modern markets. Pesticide residue analysis was performed using gas chromatography–mass spectrometry (GC–MS) to detect the active ingredients chlorpyrifos and profenofos. The results showed that chlorpyrifos residues, both methyl and ethyl forms, were not detected in any of the baby orange samples. Profenofos residues were detected in several samples; however, their levels were below the maximum residue limits specified in SNI 7313:2008. Overall, baby oranges marketed in both traditional and modern markets in Surabaya City are considered safe for consumption. Nevertheless, the presence of low levels of pesticide residues indicates the need for prudent pesticide use and continuous monitoring to ensure food safety for consumers.